Improving Digital Literacy and Student Learning Outcomes in Border School - Nawawi Nawawi; Niken Eka Priyani (Sustainable, 2023)
This study aims to improve digital literacy and learning outcomes using Augmented Reality applications developed by the Pusdatin Kemendikbudristek and Education Game Gernasila, a learning innovation created by researchers in the form of android applications. The method used is Class Action Research, as many as two cycles. The sample in this Class Action Research was 18 students in grade II at SDN 29 Idai, Sintang Regency, West Kalimantan, Indonesia. The stages of research include; planning, action, observation, and reflection. The results showed that the average student learning outcome in Cycle I were 60, while in Cycle II, it increased to 80. The average observation results of Augmented Reality in Cycle I were 70%, while the results of using the education game gernasila in Cycle II were 90%. The difference between Cycle 1 and Cycle 2 is 20%. It can be concluded that Augmented Reality developed by the Pusdatin of the Ministry of Education and Culture and Edugame Gernasila can improve student learning outcomes and digital literacy in schools located in underdeveloped areas and the borders of Indonesia.